The Spread of Academic Boredom Model in the Context of Mathematics Lessons: Epidemiological Approach - Suzana, Yenny; Irwansyah, Budi; Setambah, Mohd Afifi Bahurudin; Mulyono, Mulyono; Maulida, Iyana (Universitas Muhammadiyah Mataram, 2026)
Boredom in educational contexts seems to be a universal academic emotion, and one that is frequently experienced by students across age groups, educational needs, and ethnicity However, despite its significance in the context of mathematics lessons, academic boredom is rarely studied, especially in terms of mathematical modeling. This article proposes a dynamic model of the spread of academic boredom in the context of mathematics lessons using an epidemiological approach, taking a case study in the middle school students. This model divides the student population into four subpopulations or compartments: susceptible (S), exposed (E), infected (I), and recovered (R) from academic boredom in the context of mathematics lessons. The transition process between subpopulations or compartments is influenced by social interactions between students. By using theoretical assumptions that refer to general patterns of social behavior dynamics in adolescents and consideration of the educational context, we explore the model behavior for the spread of academic boredom in the context of mathematics lessons using sensitivity analysis and scenario-based simulation methods. The simulation results indicate that the strength of social interactions between students significantly influences the spread of academic boredom in the context of mathematics lessons. The results of this study provide insights for the policy makers in the middle school students in designing more effective strategies to mitigate academic boredom among students, especially in the context of mathematics lesson. This study opens up opportunities for further, more empirical research by incorporating actual data regarding the decisions of students why they have academic boredom.